Outcome of Corrective Dome Osteotomy for Cubitus Varus Deformity - Jha, Ranjib Kumar; Thapa, Santosh; Singh, Dhiraj (Journal of Nobel Medical College, 2019)
Background: The cubitus varus deformity is one of the most common late complications of fracture supracondylar area of humerus in children. Various corrective osteotomies are used of which lateral closed wedge osteotomy is commonly done which has its own disadvantages like lateral condylar prominence, difficulty in achieving correction and limitation of movement. Dome osteotomy is a versatile technique to achieve correction of deformity in all planes and to overcome these above complications. The aim of this study was to evaluate the results of dome osteotomy for correction of post-traumatic cubitus varus deformity of elbow in children. Materials and Methods: The study included 18 children between 6-13 years of age of both sex with malunited supracondylar fracture of distal humerus having cubitus varus deformity. After appropriate pre- operative assessment, dome osteotomy was done by posterior approach. In pre and post operative x-ray carrying angle and lateral condylar prominence Index (LCPI) were calculated. Patients were re-assessed at complete union and results were calculated. Results: In this study of 18 patients, 12 were males and 6 were females. The age ranged from 6-13 yrs with average of 8.4yrs. The average correction of carrying angle was from -22.4 degree to +10 degree. LCPI changed post operatively ranging from -8.6% to +3.25%, average -2.9%. There were no significant complications. Fifteen patients had excellent outcome and 3 had good outcome. Conclusion: The results in our study concluded that dome osteotomy for cubitus varus is safe and effective method and give cosmetically more acceptable elbow.